2023
DOI: 10.3758/s13415-023-01096-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing locus coeruleus-norepinephrine accounts of working memory, attention control, and fluid intelligence

Abstract: The current set of studies examined the relationship among working memory capacity, attention control, fluid intelligence, and pupillary correlates of tonic arousal regulation and phasic responsiveness in a combined sample of more than 1,000 participants in two different age ranges (young adults and adolescents). Each study was designed to test predictions made by two recent theories regarding the role of the locus coeruleus-norepinephrine (LC-NE) system in determining individual differences in cognitive abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 128 publications
2
7
0
Order By: Relevance
“…The correlation between P3b amplitude and working memory accuracy in the present study is more likely related to a shared impact of attentional allocation on P3b amplitude and working memory encoding. By analogy, pupil dilation is also enhanced for oddballs, correlated with working memory performance, and linked with locus coeruleus activity (Aminihajibashi et al, 2019;Eckstein et al, 2019;Gilzenrat et al, 2010;Murphy et al, 2011;Robison et al, 2023;Robison & Unsworth, 2019;Zokaei et al, 2019). However, this does mean that the mechanisms that produce pupil dilation are the same as the mechanisms that encode information into working memory.…”
Section: Decoding Resultsmentioning
confidence: 99%
“…The correlation between P3b amplitude and working memory accuracy in the present study is more likely related to a shared impact of attentional allocation on P3b amplitude and working memory encoding. By analogy, pupil dilation is also enhanced for oddballs, correlated with working memory performance, and linked with locus coeruleus activity (Aminihajibashi et al, 2019;Eckstein et al, 2019;Gilzenrat et al, 2010;Murphy et al, 2011;Robison et al, 2023;Robison & Unsworth, 2019;Zokaei et al, 2019). However, this does mean that the mechanisms that produce pupil dilation are the same as the mechanisms that encode information into working memory.…”
Section: Decoding Resultsmentioning
confidence: 99%
“…Thus, as Robison (2017a, 2017b) propose and subsequently demonstrate, people who exhibit more fluctuations in arousal from trial to trial should exhibit lower cognitive performance. Indeed, these two measures (TEPR magnitude and pretrial pupil variability) consistently correlate with individual differences in performance in a wide variety of tasks, including measures of attention control, working memory, and long-term memory, (Aminihajibashi et al, 2020;Madore & Wagner, 2022;Miller et al, 2019;Robison & Brewer, 2020, Robison & Brewer, 2023Robison & Unsworth, 2019Unsworth & Miller, 2023; 6 PUPILLARY CORRELATES OF INDIVIDUAL DIFFERENCES IN N-BACK performance correlates with intensity, consistency, or both, then the framework can apply to a broader array of cognitive domains than previously thought.…”
Section: Pupillary Correlates Of Individual Differences In N-back Tas...mentioning
confidence: 85%
“…At the level of individual differences, attention control and working memory capacity are closely related, yet distinct constructs. In latent variable analyses, they tend to share about 50% of their variance (Burgoyne et al, 2023;Draheim et al, 2022Draheim et al, , 2023Robison et al, 2023;Robison & Unsworth, 2017, 2018Unsworth et al, 2014;Unsworth & Spillers, 2010). Given those definitions, it stands to reason that attention capture should be negatively correlated with attention control and working memory capacity: people with relatively strong attention control and high working memory capacity should show less susceptibility to attentional capture.…”
Section: Individual Differences In Attention Capture Control and Work...mentioning
confidence: 99%
“…Fortunately, there are potential ways to resolve both psychometric issues -those with measuring attention control and those with measuring attention capture 1 . First, over the past several years, major strides have been made in the improvement of measurement approaches to attention control (Burgoyne et al, 2023;Draheim et al, 2021Draheim et al, , 2023Robison et al, 2023;. These studies have demonstrated that attention control can be measured reliably, both within and across measurement occasions, and the measures intercorrelate to the extent that they form a coherent latent-level factor.…”
Section: Individual Differences In Attention Capture Control and Work...mentioning
confidence: 99%
See 1 more Smart Citation